A plasma protein profile of antidepressant response to omega-3 fatty acids - Lindahl, Jesper; Stiernborg, Miranda; Ventorp, Filip; Suneson, Klara; Söderberg Veibäck, Gustav; Tjernberg, Johanna; Ståhl, Darya ; 0000-0002-8511-1791; Hjärn, Marie; Lavebratt, Catharina; Lindqvist, Daniel (Progress in Neuro-Psychopharmacology and Biological Psychiatry, 2025)
Background: Previous studies suggest an antidepressant effect of omega-3 fatty acids (n-3 PUFAs). This effect may be larger in patients with low-grade inflammation, defined as mild elevations of high sensitivity C-reactive protein or other commonly used inflammatory markers. The antidepressant mechanisms of n-3 PUFAs are not fully understood but may involve modulation of immunometabolic processes and neurotrophic effects. Here we investigated inflammatory and cardiometabolic biomarkers in patients with major depressive disorder (MDD) and controls, how these biomarkers change with n-3 PUFA treatment, and their association with antidepressant response. Methods: Ninety-four MDD patients were treated with 2.2 g eicosapentaenoic acid, 400 mg docosahexaenoic acid, and 800 mg other omega-3 fatty acids per day, added to stable antidepressant treatment for 8 weeks. Inflammatory and cardiometabolic plasma markers were assayed in MDD patients, before and after n-3 PUFA treatment, and in healthy controls (n = 76) using proximity extension assay technology. Treatment response was defined as ≥50 % reduction on the 17-item Hamilton Depression Rating Scale. Partial least squares discriminant analysis identified plasma proteins with differential levels between patients, controls, responders, and non-responders. Results: After adjusting for relevant covariates and multiple comparisons, baseline levels of several biomarkers associated with immunometabolic functions and neurotrophic processes differed significantly between MDD patients and controls and between n-3 PUFA responders and non-responders. Some of these biomarkers, related to cell-cell communication and neurotrophy, increased significantly with treatment. Conclusion: These findings provide new insights into the antidepressant mechanisms of n-3 PUFAs. Consistent with previous reports, we found evidence of pre-treatment immune activation in responders compared to non-responders, which could be used to personalize antidepressant n-3 PUFA treatment.
Keywords: Cardiometabolic biomarkers; Inflammation; Major depressive disorder; N-3 PUFAs